Classroom quiz app - Konganda, Hemala (Kansas State University, 2014)
As a part of enhancing Teaching and Learning in class, this project implements a Student Response System (SRS) by providing interactive in class quizzes between Students and Instructors by the use of a smart device. The application of this project is limited to the scope of android devices. This application includes a way in which the Instructor can enter his questions and answer for the quiz and the Student receives these questions instantly, allowing the student to choose his answer to the best of his knowledge. The answers are then validated and visualized. Based on which the Instructor implements the concept of Talk to your Partner (TTYP). The Instructor would have the option of deciding if he wants to pair the users either randomly or based on their result of the previous question.
Keywords: Android Information Science; Computer Science (0984)